Graftings, Reweavings and Interpretation: The Auchinleck Middle English Breton Lays in Manuscript and Edition - Anne Laskaya (Etudes Epistémè)
This essay argues that the material textual context provides a framework for reading the Middle English Breton Lays in the Auchinleck MS and in contemporary editions. The lays in the Auchinleck contribute to an understanding of the manuscript as a fulcrum point between English and French/Anglo-Norman cultural productions. The textual environment further supports a nuanced reading of the lays in relation to both literary legacy and historical context. Literary content, linguistic elements, codicological features, and the Auchinleck’s visual program align it with both an Anglo-Norman manuscript tradition as well as with an emerging Middle English vernacular reading audience. Although frequently considered a response to, and encouragement of, an emerging English ‘nation,’ evidence drawn from the large repository of textual and literary evidence suggests that the manuscript and its surviving texts function more as a pivot point, looking back, looking at the present, and looking toward the future in a complex contrapuntal performance. An ‘envoy’ to the argument focused on the manuscript context, considers the contours of three modern editions of the lay material, probing their organizational programs and uncovering ways the presentation of these texts in contemporary editions may shape our interpretive work as readers of the Middle English Breton lays.